A Rare Presentation of HIV-Negative Plasmablastic Lymphoma: A Diagnostic Dilemma. (13th February 2019) - Kessler, Alaina J.; Marcellino, Bridget K.; Niglio, Scot A.; Petersen, Bruce E.; Malone, Adriana K.
Abstract : Plasmablastic lymphoma (PBL) and plasmablastic plasma cell myeloma (PCM) have many overlapping characteristics. Clinical correlation can help make the distinction between the two entities. Human immunodeficiency virus- (HIV-) negative PBL is a rare disease, making the diagnosis more challenging. While there is no standard of care for PBL, current recommendations include dose-adjusted EPOCH (etoposide, vincristine, doxorubicin, cyclophosphamide, and prednisone), with or without bortezomib. We report an aggressive case of HIV-negative plasmablastic lymphoma and discuss the challenge in establishing a diagnosis. We review the literature regarding this disease and current recommendations for treatment.